A moderated mediation model for body-positive online content and body image among adolescents - Kvardova, Nikol; Machackova, Hana; Smahel, David (Body image, 2022)
Body-positive online content (BPOC) has recently become widespread, yet the factors that explain its association with body satisfaction have scarcely been studied. The current study investigates the indirect association between the self-reported frequency of viewing BPOC and body satisfaction through body appreciation and the moderating roles of body-ideal internalization, self-esteem, intentional searching, and gender. Utilizing survey data from 1530 Czech adolescents aged 13-18 (M=15.4, SD=1.7, 50 % girls), the present study found limited support for an indirect connection between the frequency of viewing BPOC and body satisfaction through body appreciation. Nonetheless, an indirect association appeared among adolescents with average and above-average frequencies for intentional searching for BPOC. Other investigated moderating factors were not significant. The present findings suggest that BPOC may be positively associated with body image, but only for those who deliberately search for it. The study highlights the importance of individual moderating factors in the context of BPOC and the remaining research gaps, such as the examination of its various types and aspects and their relationship with body image.
Keywords: Body satisfaction; Male; Self Concept; Adolescents; Adolescent; sebepojetí; mužské pohlaví; průzkumy a dotazníky; obranné mechanismy; Self-esteem; mladiství; představa o vlastním těle; lidé; osobní uspokojení; ženské pohlaví; Humans; Body-ideal internalization; Defense Mechanisms; Body appreciation; Body Image; Female; Surveys and Questionnaires; Personal Satisfaction; Body-positive online content